Cortical Hemodynamic Responses Under Focused Ultrasound Stimulation Using Real-Time Laser Speckle Contrast Imaging - Yuan, Yi; Zhao, Yanchao; Jia, Hongshuai; Liu, Mengyang; Hu, Shuo; Li, Yingwei; Li, Xiaoli (Frontiers in Neuroscience, 2018)
Although there is increasing use of focused ultrasound stimulation (FUS) in brain studies, the real-time changes of the cerebral blood flow due to FUS remain unclear. In this study, we developed a novel scheme combining FUS and laser speckle contrast imaging, which can be used to measure the cerebral blood flow caused by FUS in real time. The results showed that the change of cerebral blood flow increased from 0 s to 30 s and reached up to the maximum of 115.1 ± 6.5% at 30 s and then decreased gradually from 30 s to 60 s. This study demonstrates that FUS was able to increase cerebral blood flow and alter cortical hemodynamic responses, which indicates that FUS is a potential non-invasive method to study ischemic stroke rehabilitation.